Theory and Realization of Secondary Task Assignment for Multi-UAV Pickup Based on Green Scheduling. (31st January 2021) - Liu, Shunqi; Fang, Xi; Guo, Yi; Liu, Chenwei; Yang, Jian
Abstract : The development of artificial intelligence technology has brought changes to various industries. Under the concept of green sustainable development, how to use the progress of science and technology to implement low-carbon strategies is a problem that every enterprise should consider. Aiming at the problem of picking up goods in logistics industry, this paper proposed a secondary task assignment theory for multiple unmanned aerial vehicle (Multi-UAV) based on green scheduling. The theory greatly improves the utilization rate of unmanned aerial vehicle (UAV) and reduces the energy consumption. We analyzed the advantages and disadvantages of local optimal algorithm and global optimal algorithm in time and energy consumption. Through repeated experiments in different ranges, we have well verified the high efficiency and general applicability of this theory, which can provide theoretical and practical implications for logistics enterprises using UAV to achieve low-carbon sustainable development in the future.